ENDOGAMY IN ISLAMIC BOARDING SCHOOL CARETAKER FAMILY: A MASLAHAH POINT OF VIEW - Kudrat Abdillah; Silmah Fathimiyah (Asy-Syari'ah, 2022)
Abstract: Kyai and their family, as boarding school caretakers, become the leading role models in religious practice, including marriage. In Sumenep, Madura, some of these families practice endogamous marriage. This makes the assumption in society that the tradition of endogamous marriage continues to be preserved. This study aims to describe the endogamous marriage tradition in Boarding Schools in Sumenep from the perspective of al-Tufi’s Maslahah Theory. The researcher uses empirical legal research and case studies as his approach. The results show that the existing tradition of endogamous marriage is carried out by arranged marriage and is intended to safeguard assets, maintain lineage (nasab), and sustain the boarding school. According to al-Tufi’s Maslahah theory, the tradition has a beneficial value, although no al-Quran verses or hadith command endogamous marriage. The benefit is manifested in the goal for the continuity and development of education in the Islamic boarding school institution owned by the parents. However, there are negative impacts that need to be considered, such as hostility between families caused by unsuccessful matchmaking and the potential for abnormal or disabled children.Abstrak: Kyai dan keluarga pesantren menjadi panutan dalam praktik keagamaan, tak terkecuali perkawinan. Perkawinan antar keluarga pesantren yang terjadi di Sumenep, Madura, menimbulkan asumsi di dalam masyarakat bahwa tradisi perkawinan endogami terus dilestarikan. Penelitian ini bertujuan untuk menggambarkan fakta tradisi perkawinan endogami pada keluarga pesantren di Kota Sumenep dalam perspektif Maslahah al-Tufi. Peneliti menggunakan jenis penelitian hukum empiris dan studi kasus sebagai pendekatannya. Hasil penelitian ini menunjukkan bahwa tradisi perkawinan endogami yang ada pada kalangan keluarga pesantren di Sumenep dilakukan dengan cara perjodohan yang bertujuan untuk menjaga harta, menjaga keturunan (nasab), dan menjaga keberlangsungan lembaga pesantren. Berdasarkan teori Maslahah al-Tufi, tradisi perkawinan endogami tersebut memiliki nilai kemaslahahan, meskipun tidak ada dalil yang mewajibkan untuk melakukan perkawinan endogami. Nilai ini termanifestasi pada tujuan untuk menjaga keberlangsungan dan pengembangan pendidikan di lembaga pesantren yang dimiliki orangtuanya. Meski demikian, keluarga perlu mempertimbangkan dampak negatif yang mungkin muncul, seperti permusuhan di antara (dua) keluarga akibat perjodohan yang gagal dan adanya potensi lahirnya keturunan yang cacat.